Sensing-then-transmission slot scheduling optimization for opportu-nistic spectrum access under the interference constraint of primary us-ers - Jing ZHANG; Yin LU; Xi-qi GAO; Fu-chun ZHENG (Tongxin xuebao)
A sensing-then-transmission slot scheduling scheme for opportunistic spectrum access under the interference constraint of primary users (PU) was proposed.First,the throughput of the cognitive radio system (CRS) with channel handoff mechanism and the interference ratio to PU were deduced.An optimization model combined the sensing time and sensing period was also set up.Then,the optimal sensing time and sensing period were derived by maximizing the throughput of the CRS subject to both interference ratio and sensing qua ity constraints.Based on the analysis,a time slot scheduling scheme was finally proposed.The achievable maximum throughput of the CRS was derived too.Simulation results indicate that the proposed slot scheduling scheme can enhance the throughput of the CRS,and fit the changes of interference ratio and sensing quality constraints better.